The Correlation of Students’ Emotional Intelligence, Sentence Structure Mastery and Writing Ability - Tri Lestari Ida; Andri Wicaksono; Sri Wahyuningsih (IJLHE: International Journal of Language, Humanities, and Education, 2021)
This study aims to determine whether there is a correlation between (1) emotional intelligence and the ability of writing news texts, (2) sentence structure mastery and the ability of writing news texts, (3) emotional intelligence and sentence structure mastery with the ability of writing news texts. This research was conducted at SMP Negeri 1 Bangunrejo, Lampung Tengah, from January to May 2021. The research method used was a survey method with correlational techniques. The population of this research were the Eight grade of students SMP Negeri 1 Bangunrejo. The sample of 44 students was taken by simple random sampling. The instruments to collect data were a test of the ability of writing news texts, an emotional intelligence questionnaire, and a test of mastery of sentence structure. The data analysis technique used is regression and correlation (simple, multiple). The results of the analysis show that (1) there is a significant positive correlation between emotional intelligence (ry.1 = 0.74 at the level of significance a = 0.05 with n = 80 the result is rt = 1.66), (2) there is a positive correlation between sentence structure mastery and the ability of writing news text (ry.2 = 0.79) at a significant level of a = 0.05 with n = 80 the result is rt = 11.38), (3) there is a significant positive relationship between emotional intelligence and mastery of sentence structure with the ability of writing news texts (Ry.12 = 0.837 at a significance level of a = 0.05 with n = 80 the result is Ft = 3.12). In the significance test of the multiple regression coefficients Y over X1X2 produces t1 = 2.37, t2 = 5.57. From the distribution list t with dk 77 (a = 0.05) obtained tt of 1.66 which turns out to be t1 > tt and t2 > tt. It means that the regression coefficient related to X1X2 is significant.